2016
DOI: 10.1038/ki.2015.291
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of H3K9 histone methyltransferase G9a attenuates renal fibrosis and retains klotho expression

Abstract: H3K9 methyltransferase G9a is reportedly induced by transforming growth factor-β1 (TGF-β1) and has an important role in the development of epithelial-mesenchymal transposition in cancer cells. Since the transcriptional activity of the Klotho gene is regulated by H3K9 modification, we investigated the effects of G9a on renal fibrosis and klotho expression. G9a levels were significantly upregulated by day 7 in the kidneys of unilateral ureteral-obstructed mice, but this was inhibited by TGF-β1-neutralizing antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 53 publications
3
69
0
Order By: Relevance
“…In terms of peritoneal fibrosis, previous studies have reported that a histone acetyltransferase inhibitor, C646, suppresses TGF-β1-induced fibrotic changes in HPMCs [28], and that suberoylanilide hydroxamic acid, a histone deacetylase inhibitor, attenuates peritoneal fibrosis in mice via induction of bone morphogenetic protein (BMP)-7 [29]. Notably, our previous report demonstrated that TGF-β1-induced H3K9me1 is responsible for the progression of renal fibrosis [19]. Because histone methylation is regulated by specific enzymes, its regulation is considered to be a more specific therapy for peritoneal fibrosis than regulation of enzymes involved in other histone modifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of peritoneal fibrosis, previous studies have reported that a histone acetyltransferase inhibitor, C646, suppresses TGF-β1-induced fibrotic changes in HPMCs [28], and that suberoylanilide hydroxamic acid, a histone deacetylase inhibitor, attenuates peritoneal fibrosis in mice via induction of bone morphogenetic protein (BMP)-7 [29]. Notably, our previous report demonstrated that TGF-β1-induced H3K9me1 is responsible for the progression of renal fibrosis [19]. Because histone methylation is regulated by specific enzymes, its regulation is considered to be a more specific therapy for peritoneal fibrosis than regulation of enzymes involved in other histone modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Among epigenetic regulations, methylation of the histone tail is regulated by specific enzymes [18], indicating that TGF-β1-induced histone methyltransferases are therapeutic targets for peritoneal fibrosis. Recently, we have demonstrated that TGF-β1-induced G9a is responsible for renal fibrosis through mono-methylation of lysine 9 in histone H3 (H3K9me1), but not di-methylation (H3K9me2) [19]. G9a-induced H3K9 methylation causes transcriptional silencing [20], raising the possibility that BIX01294, a selective inhibitor of G9a, can suppress the loss of cellular properties and subsequent fibrotic processes through inhibition of H3K9me1.…”
Section: Introductionmentioning
confidence: 99%
“…Histone mark regulation of fibroblast-like differentiation is recognized in a multiplicity of pathologies including liver (Mann et al, 2010; Perugorria et al, 2012), nasal mucosa (Cho et al, 2012), cornea (Zhou et al, 2010), lung (Guo et al, 2009), and kidney (Irifuku et al, 2016) fibrosis. Consistent with this, TGF-β1 has been shown to enrich various active histone marks and decrease levels of repressive marks at pro-fibrotic gene promoters in renal mesangial cells (Sun et al, 2010; Yuan et al, 2013), epithelial cells (Sasaki et al, 2016), and fibroblasts (Irifuku et al, 2016; Sasaki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…*P < 0.05, **P < 0.01, ***P < 0.001, as tested by one-way ANOVA with Bonferroni's post-hoc test. dysregulation of its splicing as possible mechanisms contributing to Klotho downregulation, in addition to transcriptional regulation (16,53,54), epigenetic regulation (55)(56)(57), and miRNAs (58,59).…”
Section: Discussionmentioning
confidence: 99%